PERBANDINGAN PENANGANAN MINORITAS AHMADIYAH DI KOTA YOGYAKARTA DAN KOTA HAIFA - , GUSTI HENING PUSTHIKAPUTRA; , Drs. Samsu Rizal Panggabean, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ahmadiyya is a sect by most Muslims in the world are considered heretical. In Indonesia, through the SKB (Joint Decree) Three ministers said that the Indonesian Ahmadiyah is deviant, however, this decree returned to the area to be used or not, according to the circumstances of the country. This poses a problem to create a conflict between Ahmadis and non - Ahmadis. In Yogyakarta, in 2012 and had been a tension between the MUI (Indonesian Ulema Council) with the Indonesian Ahmadiyah Movement (GAI) in Baciro. This is caused by the GAI hold annual grand recitation. MUI demanding the dissolution study with allegations that Ahmadyah GAI heresy, as outlined in the 2005 MUI fatwa of apostasy GAI and JAI. Although it is not until there is violence, but it is becoming a \" shock \" to Yogyakarta that before this looks serene in religious life. Kababir in Haifa is the \" hometown \" of Ahmadiyah followers in Israel. Kababir considered a mixed environment, and Haifa city officials see it as a model of coexistence. Most Israelis know very little about this sect, which is considered to be peaceful and non - proselytizing. Haifa Mayor Yona Yahav so far to call them \" Arab Reform. \" Society motto is \" Love for all , hatred for none.\"